PERCEIVED ENJOYMENT, PERCEIVED RISK, AND SCARCITY MESSAGE ON IMPULSIVE BUYING IN LIVE SHOPPING IN E-COMMERCE - Lita Amanah Siregar; Carunia Mulya Firdausy (Graduate Program of Universitas Tarumanagara, 2024)
ABSTRACT Live shopping has gained significant traction as the e-commerce sector continues to advance, incorporating interactive and real-time features to improve the online shopping experience. This research investigates the impact of perceived enjoyment, perceived risk, and scarcity messages on impulsive buying behavior within live shopping e-commerce. The study employs a descriptive analysis approach with a quantitative methodology. Convenience sampling was utilized to select participants based on predetermined criteria. Data were collected via an online questionnaire using a 1-7 points Likert scale, encompassing 20 indicators. A total of 250 respondents in Jabodetabek who had engaged in impulsive purchases during live shopping participated in the study. The data were analyzed through Structural Equation Modeling (SEM) using the SmartPLS 3.0 software. The results indicate that perceived enjoyment, perceived risk, and scarcity messages have a significant and positive effect on impulsive buying in live shopping environments. These findings provide valuable insights into consumer behavior in live shopping settings, offering strategic implications for enhancing the e-commerce live shopping experience. Moreover, the study suggests directions for future research to further explore these factors in online shopping behavior.